2021
DOI: 10.21037/tlcr-20-1173
|View full text |Cite
|
Sign up to set email alerts
|

Validation of multivariable lung cancer risk prediction models for the personalized assignment of optimal screening frequency: a retrospective analysis of data from the German Lung Cancer Screening Intervention Trial (LUSI)

Abstract: Background: Current guidelines for lung cancer screening via low-dose computed tomography recommend annual screening for all candidates meeting basic eligibility criteria. However, lung cancer risk of eligible screening participants can vary widely, and further risk stratification could be used to individually optimize screening intervals in view of expected benefits, possible harms and financial costs. To this effect, models have been developed in the US National Lung Screening Trial based on self-reported lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…While these studies have shown initial promising results, to our knowledge, external validation of these models has been limited thus far. 120 study. [121][122][123]…”
Section: Determination Of the Screening Intervalmentioning
confidence: 95%
“…While these studies have shown initial promising results, to our knowledge, external validation of these models has been limited thus far. 120 study. [121][122][123]…”
Section: Determination Of the Screening Intervalmentioning
confidence: 95%
“…Conceivably, in organized screening programs such model predictions could be further improved by the inclusion of spirometry lung function tests. Likewise, ascertainments of spirometric abnormality may also be integrated in models predicting lung cancer risk, in view of determining personally optimized screening intervals ( 56 - 58 ), modulating screening frequency according to risk of having lung cancer detected upon a next screening visit.…”
Section: Discussionmentioning
confidence: 99%
“…Using a minimal threshold for LC risk as a general eligibility criterion ensures that financial costs, as well as the number of individuals that needs to be screened (NNS) and that exposed to the possible of harms of screening (radiation exposures; risk of false-positive findings), remains within acceptable limits relative to the number of LC cases detected within a screening program. For individuals already participating in a screening program (i.e., who meet a minimal-risk criterion for having LC) estimates of LC risk can be used further to determine individually more optimized time intervals between successive screenings ( 40 - 42 ). Finally, having a sufficiently low risk estimate for short- to medium-term (5- to 10-year) mortality (i.e., having a sufficiently high remaining life expectancy) can be used as a criterion for individualized recommendations as to whether LC screening should be further pursued or dis-continued.…”
Section: Discussionmentioning
confidence: 99%